Temporal Trends in Surgical Resection Rates and Biologic Prescribing in Crohn's Disease: A Population-based Cohort Study. (25th August 2020) - Jenkinson, P W; Plevris, N; Siakavellas, S; Lyons, M; Arnott, I D; Wilson, D; Watson, A J M; Jones, G-R; Lees, C W
Abstract: Background: The use of biologic therapy for Crohn's disease [CD] continues to evolve, however, the effect of this on the requirement for surgery remains unclear. We assessed changes in biologic prescription and surgery over time in a population-based cohort. Methods: We performed a retrospective cohort study of all 1753 patients diagnosed with CD in Lothian, Scotland, between January 1, 2000 and December 31, 2017, reviewing the electronic health record of each patient to identify all CD-related surgery and biologic prescription. Cumulative probability and hazard ratios for surgery and biologic prescription from diagnosis were calculated and compared using the log-rank test and Cox regression analysis stratified by year of diagnosis into cohorts. Results: The 5-year cumulative risk of surgery was 20.4% in cohort 1 [2000–2004], 18.3% in cohort 2 [2005–2008], 14.7% in cohort 3 [2009–2013], and 13.0% in cohort 4 [2014–2017] p <0.001. The 5-year cumulative risk of biologic prescription was 5.7% in cohort 1, 12.2% in cohort 2, 22.0% in cohort 3, and 44.9% in cohort 4 p <0.001. Conclusions: The increased and earlier use of biologic therapy in CD patients corresponded with a decreasing requirement for surgery over time within our cohort. This could mean that adopting a top-down or accelerated step-up treatment strategy may be effective at reducing the requirement for surgery in newly diagnosed CD.